2020
DOI: 10.3389/fpubh.2020.561273
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends of Physical Fitness in Twenty-Five Birth Cohorts of Slovenian Children: A Population-Based Study

Abstract: In Slovenia, the national SLOfit surveillance system of the somatic and motor development of children and youth has been enabling researchers to observe the developmental trends of the entire population of school-aged children since 1987. The national database currently incorporates over 7.2 million sets of measurements of eight fitness tests and three anthropometric measurements. Since 1991, as in the rest of the world, in Slovenia, there is a common perception that the physical fitness of contemporary childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 31 publications
(33 reference statements)
3
19
1
Order By: Relevance
“…A great majority of adolescents do not meet the recommendations for moderate-to-vigorous PA (MVPA) [ 6 ] despite well-documented positive impact on skeletal [ 7 , 8 ], metabolic [ 9 , 10 ], cardiovascular [ 11 ], and psychosocial [ 12 ] health. In addition, physical fitness (PF) levels appears to be declining in this population [ 13 , 14 ]. Accordingly, childhood and adolescence is a critical period for the development of PF [ 15 ] and adolescence has been identified as one of the stages that may play a critical role in the development and persistence of obesity and related comorbidities into adulthood [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A great majority of adolescents do not meet the recommendations for moderate-to-vigorous PA (MVPA) [ 6 ] despite well-documented positive impact on skeletal [ 7 , 8 ], metabolic [ 9 , 10 ], cardiovascular [ 11 ], and psychosocial [ 12 ] health. In addition, physical fitness (PF) levels appears to be declining in this population [ 13 , 14 ]. Accordingly, childhood and adolescence is a critical period for the development of PF [ 15 ] and adolescence has been identified as one of the stages that may play a critical role in the development and persistence of obesity and related comorbidities into adulthood [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that risk factors for diseases usually manifest during adulthood, studies have shown that childhood and adolescence are critical time-points for maintaining ‘good’ lifestyle habits and develop high physical fitness levels 9 due to well-tracking characteristics of physical fitness from childhood to adulthood 1 . However, a common perception has been embraced that the physical fitness in youth has declined because of more time spent in sedentary behavior, lack of physical activity and consuming fat-rich food 10 . Such decrease is, however not uniform in different countries and physical fitness modalities 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Secular trends of physical fitness in children and adolescents have been well-studied in the past decades 10 , 12 35 . In general, values in cardiorespiratory, muscular and flexibility fitness decline, and values in body-mass index (as a measure of body size) increase, especially in work that goes back further in time (between 1960 and 1980s), while there have been conflicting findings for motor fitness in terms of a decrease, increase or stagnation 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is continued debate on the best, or rather, most accurate model to assess 20mSRT as a predictor of CRF (Welsman and Armstrong, 2019). Knowing these limitations, it remains that initial decreases in CRF were reversed from 2003 to 2013 (∼8.2%), across all ages, in both sexes and inline with overall secular trends of physical fitness in Slovenia during that time (Potočnik et al, 2020). Indeed, CRF increased ∼5.4% across the 20-year (1993-2013) period of study.…”
Section: Secular Trends In Sloveniamentioning
confidence: 99%